INVESTIGATING EFL LEARNERS’ “INDONGLISH” USAGE BY ENGLISH DEPARTMENT STUDENTS: A QUALITATIVE STUDY - Ikrar Genidal Riadil (International Journal of Humanity Studies (IJHS), 2021)
The aim of this study was to analyze the specific vocabulary in the Indonglish phenomenon that the Tidar University students use in the educational environment at Tidar University, the meaning that exists in Indonglish at Tidar University, and the impact Indonglish usage in the use of Indonesian is correct and right in the environment education in universities in Tidar University in a signification effort Indonesian. Indonglish is a term often used for the use of the English language which is nuanced by Indonesian culture. Indonglish study focuses on environmental education, particularly in higher education that is not only limited to the academic setting but also non-academic. The researchers used qualitative research, the data of this research were a wide range of speeches acquired in an educational environment, especially in Java, in which there are forms of language linguistically mixed Indonesian and English. Locational data source of this research were the perpetrators of students in environmental education at Tidar University. The result is the 5th semester students produced 35 Indonglish vocabulary and the 7th semester students produced 31 Indonglish vocabulary. The basic assumption for determining the locational data sources was the consideration that the students, faculties, and staffs had a varied background of social, economic, cultural so that it was expected to describe the condition of society. The data analysis was conducted by applying the distributional method that was commonly done in linguistics. The method of analysis was done after the data were collected and properly classified. Furthermore, the interpretation of the data was done.  Then, the interpreted data were presented informally.